Psychological Burnout and Adaptation Strategies for Health Practitioners during the COVID-19 Pandemic in Al-Kamel Governorate - Alsolami, Abdaltawab Fazaa; Yusef, Muhammad Abdulrahman (Journal of Educational and Psychological Sciences, 2022)
This study aims at measuring the level of psychological burnout and adaptation strategies of health practitioners during the COVID-19 pandemic in Al-Kamel Governorate. The study sample included 155 health practitioners in Al-Kamel Governorate. The Maslach psychological burnout scale was used as a study tool, which was developed by (Al-Sharif, 2020), as well as developing the adaptation strategies tool which consisted of 24 paragraphs divided into four dimensions: knowledge acquisition, problem solving, social support, and problem avoidance. The researcher adopted the descriptive (analytical) approach in the study. The findings of this study revealed that the psychological burnout of repetition resulted in the equivalent of (2.5) days per week, with a lower intensity than the average. The findings of the most common adaptation strategies used, revealed a statistically significant difference between the study sample of the level of psychological burnout (repetition) according to years of experience and specialization in the first, second and third dimensions. However, no significant differences were shown in terms of severity and the other dimensions. Also, no differences were detected in relation to gender. In addition, there are differences in health practitioners' adaptation strategies based on years of service, gender, and specialization. Moreover, in view of the Corona pandemic in Al-Kamel Governorate, there was no significant correlation between burnout levels and health practitioners' adaptation strategies. The researcher recommended that we should try to find preventive and treatment programs and conduct specialized courses for health practitioners to provide them with skills that enable them to overcome the difficulties in work.
Keywords: Psychological burnout; Adaptation strategies; Health practitioners; Corona pandemic